Soviet-Vietnam Relations and the Role of China 1949-64: Changing Alliances, 1st edition - Olsen, Mari (Routledge, 2020)
This new book analyzes how the Soviet leadership evaluated developments in Soviet-Vietnamese relations in the years from 1949 to 1964.